Archival resonances: embodied libraries and the corporeal lives of sonic effects. Issue 2 (3rd July 2021) - Walker, Alison
ABSTRACT: This article examines the relationship between the postproduction sound practitioner and their library of sound files. The paucity of phenomenological accounts of digital library use means there is opportunity to use theories of embodiment as well as existing understandings of archives in order to reframe understandings of the digital library, particularly in a film sound production context. To abstract the sound library from embodiment is to miss the opportunity to further deconstruct the notion of technicity and data as divorced from the bodies of users. Film sound postproduction provides a rich canvas with which to pursue a discussion of embodied libraries. This article first examines the recording and building of a library as a creative resource; it then examines how sound files as units of a larger library archive, live multiple sonic lives across many projects. Further, the role of location, practices of library engagement, including auditioning and selection of sound, as well as metadata management are examined. In this way, the sound library becomes reconfigured as a sensory archive, and the sound file becomes the sensory kindling rich with personal meanings. These meanings are lived and re-lived, exchanged and reinvented with each new incarnation of a sound work.